The Impact of the Digital Design Process on a Traditional Design Studio Comparative Analysis on the Impact of the Digital Design Process on a Traditional Design Studio - Turan, Bulent Onur; Soygenis, Murat (ECAADE-EDUCATION & RESEARCH COMPUTER AIDED ARCHITECTURAL DESIGN EUROPE, 2009)
To apprehend and apply the design concepts is directly related to the content of the education, the participation of the students in the design process and the design media facilities. The computer as a different design media affects the design process and also the design product. Accordingly, as a considerable fact, some of the courses in the architectural education program are based on the digital medium. However, enhancing the integration between the design courses, implemented in the studios, as a main part of the architectural design education and the digital media courses is contemplated as an actual requirement. In this context, regarding to the complement enclosure of this research, considering the affection of the transformations of the design pragmatics to the design educations, the traditional and the digital design methodologies are comparative underscored, and also the contributions of the digital design methodology to the traditional way of artificial manufacturing are analyzed during the development process of the design. For this purpose, the design theories, the digital design methodologies and accordingly the investigation properties about the construction of the theoretical conceptualization of the digital methodology, the approaches about the education and the design methodologies are literally overviewed. This comparative analysis had constituted the main comprehension of this inquisition.
Keywords: Digital design; digital model; form; architectural education; design media; interaction; Architecture